Baverage Container Deposit Return System in Slovakia: Insights after One Year of Its Introduction - Jarossová, Malgorzata A.; Gubíniová, Katarína (System zwrotu kaucji za opakowania po napojach na Słowacji: spostrzeżenia po roku od jego wprowadzenia, 2022)
Every year, consumers buy more and more beverages packaged in disposable PET bottles and aluminium cans. Most of this packaging is used only once and also very often pollutes the environment due to inappropriate consumer behaviour. Deposit return systems for bottles and aluminium cans play an important role in preventing such situations, offering consumers a financial incentive, a deposit that motivates them to return used packaging. The purpose of the article was to describe consumer and company insights related to the new deposit return system for PET bottles and aluminium beverage cans in Slovakia, based on the authors’ own research and secondary research. Furthermore, the authors also wanted to show the solutions of some companies that try to facilitate to consumers the process of returning disposable packaging.
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2022, Nr 38, s. 75-89
Keywords: deposit return system; beverage packaging; Slovakia; retail chains; consumers; system zwrotu kaucji; opakowania na napoje; Słowacja; sieci handlowe; konsumenci